Enabling the Systems Engineering Education Ecosystem (SEEE). Issue 1 (26th September 2022) - Wade, Jon; Collopy, Arianne; Dagli, Cihan; Gerardo, Hortense; Wood, Kristin
Abstract: System engineering education is challenged to address the need posed by rapidly changing technology epitomized by Industry 4.0 and the digital transformation. In particular, there are relatively slow and inaccurate feedback mechanisms between the needs of employers, students and universities at the level of educational program content development. To address this issue, the Systems Engineering Education Ecosystem (SEEE) was established to create and assess the feedback mechanisms by which educators, students and employers can communicate their specific educational capabilities, desires and needs, in order to provide the dynamic feedback necessary to accelerate the evolution of graduate Systems Engineering (SE) educational programs, clearly communicate the characteristics of existing programs, provide access to relevant educational materials, and create a dynamic self‐evolving educational system. This paper describes the vision, objectives, design and development process, current status and future developments, with the intention to support a global systems engineering education ecosystem.